Inhibition of Polyamine Biosynthesis Using Difluoromethylornithine Acts as a Potent Immune Modulator and Displays Therapeutic Synergy With PD-1-blockade. Issue 8 (October 2021) - Dryja, Parker; Fisher, Carrie; Woster, Patrick M.; Bartee, Eric
Abstract : Polyamines are known to play a significant role in cancer progression and treatment using difluoromethylornithine (DFMO), an inhibitor of polyamine biosynthesis, has shown some clinical promise. It is interesting to note that, while DFMO is directly cytostatic in vitro, recent work has suggested that it achieves its antitumor efficacy in vivo by enhancing adaptive antitumor immune responses. On the basis of these data, we hypothesized that DFMO might act as an immune sensitizer to increase tumor responsiveness to checkpoint blockade. To test this hypothesis, we treated tumors with DFMO, in either the presence or absence of additional PD-1 blockade, and subsequently analyzed their immunological and therapeutic responses. Our data demonstrates that treatment with DFMO significantly enhances both the viability and activation status of intratumoral CD8 + T cells, most likely through an indirect mechanism. When combined with PD-1 blockade, this increased viability resulted in unique proinflammatory cytokine profiles and transcriptomes within the tumor microenvironment and improved therapeutic outcomes. Taken together, these data suggest that DFMO might represent a potential immunomodulatory agent that can enhance current PD-1-based checkpoint therapies. Abstract : Supplemental Digital Content is available in the text.